PENGARUH KETERLIBATAN KERJA, PENGAWASAN DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI PADA KANTOR UNIT PENYELENGGARA PELABUHAN KELAS I MOLAWE - Syamsir, Syamsir; Razak, Abdul; Yunus, Asraf (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study aims to determine and analyze the influence of job involvement, supervision, and job characteristics on employee performance at the Office of Class I Port Operator Unit in Molawe. The sample in this study consists of all employees at the Office of Class I Port Operator Unit in Molawe, totaling 54 individuals. This study uses multiple linear regression analysis. The results of the study show that: (1) Job involvement, supervision, and job characteristics have a positive and significant effect on employee performance at the Office of Class I Port Operator Unit in Molawe. (2) Job involvement has a positive and significant effect on employee performance at the Office of Class I Port Operator Unit in Molawe. (3) Supervision has a positive and significant effect on employee performance at the Office of Class I Port Operator Unit in Molawe. (4) Job characteristics have a positive and significant effect on employee performance at the Office of Class I Port Operator Unit in Molawe.